Systematic Literature Review of Lean Tools Applied to Software Development - Paz Llamocca, Melanie Briggite (2023)
Currently, the predominance of Agile frameworks in software development means that Lean applications in the IT sector are incipient or very little known. However, several authors argue that the application of Lean in software has more advantages than Agile could have, due to the scalability of the procedures. The objective of this research is to know the state of the art of the application of Lean in software development through a systematic literature review. After reviewing 19 articles, it was found that the most common Lean waste with the greatest impact on software development is waiting. The main barriers that hinder the application of Lean correspond to attitudinal components of people such as low understanding of Lean concepts. The most applied Lean tool is Kanban and the main advantage of applying Lean in software development is the improvement of team performance.